Facilities in Government Rural Schools in Punjab Require a Shift from Quantity to Quality - Singh, D. P.; Ritu (JOURNAL OF INDIAN EDUCATION, 2013)
The state of Punjab has achieved a considerable success in terms of school infrastructure. As per the Educational Development Index (EDI) 2011 prepared by National University of Educational Planning and Administration (NUEPA), Punjab is at the top in infrastructural parameters in the country followed by Pondicherry and Andaman and Nicobar Islands. Given to the fact that the facilities in schools have a direct bearing on the quality of education as well as on the overall academic environment, the present paper provides information on the availability of various facilities in the school namely the drinking water, separate toilets for girls, electricity, availability of furniture for teachers and students, the condition of school building and other basic facilities like the boundary wall, playground, library and computers etc. The study finds that there is a stark difference between the institutional facilities available in the private schools and the government schools both in terms of institutional as well as human factors such as teachers’ attitude, commitment. In spite of achieving a considerable success in terms of school infrastructure of government schools, a lot more is required to be done towards improving the quality, upkeep, community ownership and the parity at par to that of the private schools in the State.